2001
DOI: 10.1016/s0277-5387(00)00598-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural and spectral studies of 5-methyl 2-furaldehyde thiosemicarbazone and its Co, Ni, Cu and Cd complexes

Abstract: The reaction of cobalt, nickel, copper and cadmium chlorides and bromides with 5-methylfurfural thiosemicarbazone (M5FTSC) leads to the formation of two series of new complexes: [M(M5FTSC) 2 X 2 ], [M(M5FTSC)X 2 ]. They have been characterized by spectroscopic studies (infrared, 1 H NMR, and electronic spectra). The crystal structures of the free ligand M5FTSC and of the compound [CuCl 2 (M5FTSC)] have been determined by X-ray diffraction methods. For the Co(II), Ni(II) and Cu(II) complexes, the central atom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 24 publications
10
49
0
2
Order By: Relevance
“…This is a consequence of the coordination of the sulphur from the C=S(NH 2 ) group as reported earlier. 7,28 This coordination is confirmed by the presence of a new band at 380-395 cm -1 that can be assigned to (M-S) for all complexes. 28,29 In the ligand spectrum, the strong band observed at 1600 cm -1 can be assigned to (C-N) frequencies.…”
Section: Ir Spectramentioning
confidence: 63%
“…This is a consequence of the coordination of the sulphur from the C=S(NH 2 ) group as reported earlier. 7,28 This coordination is confirmed by the presence of a new band at 380-395 cm -1 that can be assigned to (M-S) for all complexes. 28,29 In the ligand spectrum, the strong band observed at 1600 cm -1 can be assigned to (C-N) frequencies.…”
Section: Ir Spectramentioning
confidence: 63%
“…O caráter parcialmente duplo da ligação C-N pode também ser facilmente evidenciado pela técnica de espectrometria de ressonân-cia magnética nuclear de hidrogênio (RMN 1 H), uma vez que os hidrogênios em NH 2 aparecem como dois sinais não equivalentes. Isto acontece devido à rotação restrita da ligação C-NH 2 por conta da dupla ligação parcial que, desta forma, torna os hidrogênios diastereotópicos 24,25 . A temperaturas elevadas (~ 323 K) estes sinais coalescem como mostra o trabalho de Ferrari e colaboradores 26 .…”
Section: Considerações Moleculares E Eletrônicasunclassified
“…Vale ressaltar que o baixo valor da banda de estiramento de C=S é devido ao seu acentuado caráter de ligação simples, e que esta pode variar de acordo com o ambiente quími-co [29][30][31][32] . Obviamente, complexos metálicos de tiossemicarbazonas mudam consideravelmente a posição destas bandas, principalmente aquelas que estão envolvidas na ligação coordenada 25,33 . Bharti e colaboradores 27 obtiveram complexos de paládio e observaram deslocamentos negativos (14-39 cm -1 ) para a banda de C=N, que aparece normalmente entre 1556-1630 cm -1 , indicando o envolvimento da função azometina na ligação coordenada, assim como para a tiocarbonila (C=S), onde as bandas foram deslocadas para freqüên-cias menores (13-35 cm -1 ).…”
Section: Considerações Moleculares E Eletrônicasunclassified
“…Schiff base metal complexes attract considerable interest and occupy an important role in the development of the chemistry of chelate systems [12,13] due to the fact that especially these with N2O2 tetradentate ligands, such systems closely resemble metallo-proteins. Survey of the literature reveals an excellent work devoted to synthesis and characterization of many metal complexes of Schiff base [14][15][16][17]. Additionally, it has been reported that Schiff bases and their first-row transition metal complexes can exhibit fungicidal, bactericidal, antiviral and antitumor activities in addition to their important roles in catalysis and organic synthesis [18][19][20].…”
Section: Introductionmentioning
confidence: 99%